Medical students’ perspectives on a longitudinal wellness curriculum: A qualitative investigation - Velez, Camila; Gendreau, Pascale; Saad, Nathalie (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2024)
Introduction: There is growing concern about the mental health status of medical students. Medical students are at a higher risk for depression, anxiety, and burnout than non-medical students. The Undergraduate Medical Education (UGME) Office of Medical Learner Affairs at McGill University developed a Longitudinal Wellness Curriculum (LWC) to foment medical students’ well-being, self-care, and adaptability.Methods: We conducted a qualitative descriptive study to explore students’ experiences with the LWC. We conducted three semi-structured focus groups involving a total of 11 medical students. We used thematic framework analysis for data analysis.Results: We found four main themes related to participants’ engagement with the curriculum: 1) diverse perceptions on curriculum relevance and helpfulness; 2) the benefits of experiential sessions, role model speakers, and supportive staff; 3) insights on student-friendly curriculum scheduling; and 4) the importance of wellness education and systemic interventions in medical education.Conclusions: Most participants found the curriculum valuable and supported its integration into the academic curriculum. Experiential and active learning, diverse approaches to wellness, small group sessions, role modeling, and student-centered approaches were preferred methods. Inconvenient curriculum scheduling and skepticism over system-level support were seen as barriers to curriculum engagement and uptake. The findings of our study contribute to the development and implementation of wellness curriculum efforts in medical education.